Future Structure of the Life-World. As an inevitable consequence of the «peer-to-peer» - Mori, Mototaka (SocietàMutamentoPolitica, 2016)
This article intends to draw theoretically a future structure of the life-world. The state interventionism in the late capitalism has been often argued by the critical theoreticians like Jurgen Habermas since the last half of the twentieth century. It was particularly the main problem how possible the life-world was in such the technologically systematized society. However, the highly technological development of telecommunication has changed our everyday life very rapidly and totally. If we know such the rapid change of coevolution between human life and technology, we have to fundamentally reconsider on the theory of life-world. Therefore, in this article I will firstly focus on the classical theory of mundane social world which Alfred Schutz presented in the early 1930s. Of course, his project of socio-phenomenology has been one of the most brilliant und important works still now. However, his theory also will have to be renewed. If we know particularly the «peer-to-peer» constellation of the computer network by the distributed anonymous persons, the classical model of life-world must be versioned up to a next theoretical level. Secondly, considering on the virtual currency like the Bitcoin, this article will show you a hypothetical aspect of transformation of the life-world. The mechanism of trust, which has been often understood as one of the most important key concepts for the community or the society, may be replaced with the computer technology of cryptographic proof. Such a theoretical examination will finally lead to an important opened problem. We will have to inquire whether such the social order will be spontaneous, or whether such the ordering will have to be decided only by the speed of computer’s central processing unit.